2019
DOI: 10.1002/jia2.25239
|View full text |Cite
|
Sign up to set email alerts
|

Retention on antiretroviral therapy during Universal Test and Treat implementation in Zomba district, Malawi: a retrospective cohort study

Abstract: IntroductionSince June 2016, the national HIV programme in Malawi has adopted Universal Test and Treat (UTT) guidelines requiring that all persons who test HIV positive will be referred to start antiretroviral therapy (ART). Although there is strong evidence from clinical trials that early initiation of ART leads to reduced morbidity and mortality, the impact of UTT on retention on ART in real‐life programmatic settings in Africa is not yet known.MethodsWe conducted a retrospective cohort study in Zomba distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
67
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(83 citation statements)
references
References 21 publications
7
67
6
Order By: Relevance
“…We found that adolescents and young adults were more at risk of attrition when compared to adults. Our findings are consistent with other studies [49][50][51][52]. Adolescents and young adults have been shown to be at high risk of attrition due to several factors, which include lack of youth-friendly services, rigid scheduling not taking into account schooling, and unavailability of peer caregivers [53,54].…”
Section: Discussionsupporting
confidence: 92%
“…We found that adolescents and young adults were more at risk of attrition when compared to adults. Our findings are consistent with other studies [49][50][51][52]. Adolescents and young adults have been shown to be at high risk of attrition due to several factors, which include lack of youth-friendly services, rigid scheduling not taking into account schooling, and unavailability of peer caregivers [53,54].…”
Section: Discussionsupporting
confidence: 92%
“…However, among patients enrolling in care in the Treat All period, retention in care among patients initiating ART within 30 days was significantly higher than those not initiating ART within 30 days after enrolment. These results are consistent with earlier studies that have described either no effect or improvement in retention in care associated with early ART initiation, including preliminary findings from the MaxART trial in eSwatini and from implementation of Treat All in Malawi [24][25][26][27][28]. In subgroup analyses, retention in care did not significantly worsen after Treat All implementation among those with more advanced HIV (as indicated by CD4 count) or among men and younger patients, who have traditionally been at risk of worse outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…Besides, our findings also show an elevated risk of LTFU among patients who started ART within seven days following diagnosis compared to those who started after 7 days following HIV diagnosis. This finding contrasts what has been reported previously [27]. One possibility for the differences could be methodological, especially in the determination of the outcomes across the studies, but also the fact that different study populations were considered.…”
Section: Plos Onecontrasting
confidence: 99%